STROKE VOLUME DYNAMICS IN MALES WITH DIFFERENT FITNESS LEVEL - Klemen Lavrenčak; Branko Škof; Radoje Milić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Stroke volume (SV) is well known as a routine clinical cardiodynamic measure. It represents the amount of blood ejected by the left ventricle in one beat. Our aim in present study was to evaluate, both, the stroke volume dynamics in males with different fitness level and the relationship between maximal SV value measured during graded exercise testing (GXT) on treadmill and VO2 max. One hundred male participants of age 43,06 ± 9.03 years, height 175 ± 8.25 cm, body mass 76.94 ± 15.42 kg, BSA 2.01 ± 0,15 m2 and peak oxygen consumption 46.55 ± 7.03 ml kg-1 min-1 volunteered to participate in this study. All tests were performed in Exercise Physiology Laboratory (University of Ljubljana, Faculty of Sport), The group of expirienced recreational runners differed from sedentary or less trained recreational runners in higher cardiac output (Q); 20.92 ± 4.57 vs 16,90 ± 4,34 l · min-1 (p ≤ 0,001), bigger SV: 136,43 ± 34,59 vs 112,04 ± 30,11 ml · beat -1 (p ≤ 0,001) and higher SI: 73,41 ± 13,42 vs 60,66 ± 11,58 ml · beat -1 · m-2 (p ≤ 0,001). Interestingly, both groups reached maximal SV at practically identical level of test (58.62 ± 17.81 % vs 59,85 ± 14,27 % VO2max). Also, the pattern of SV fall according to VO2max in both groups tested, were similar (12.08 ± 6.26 % vs 11,33 ± 6,23 %).